Fat-rich versus carbohydrate-rich nutrition in ALS: a randomised controlled study. Issue 3 (12th January 2022) - Dorst, Johannes; Doenz, Judith; Kandler, Katharina; Dreyhaupt, Jens; Tumani, Hayrettin; Witzel, Simon; Schuster, Joachim; Ludolph, Albert C
Abstract : Objective: There is growing evidence that the course of amyotrophic lateral sclerosis (ALS) may be influenced beneficially by applying high-caloric food supplements (HCSs). However, it is unknown which composition of nutrients offers optimal tolerability and weight gain. Methods: We conducted a randomised controlled study (Safety and Tolerability of Ultra-high-caloric Food Supplements in Amyotrophic Lateral Sclerosis (ALS); TOLCAL-ALS study) in 64 patients with possible, probable or definite ALS according to El Escorial criteria. Patients were randomised into four groups: a high-caloric fatty supplement (HCFS; 405 kcal/day, 100% fat), an ultra-high-caloric fatty supplement (UHCFS; 810 kcal/day, 100% fat), an ultra-high-caloric, carbohydrate-rich supplement (UHCCS; 900 kcal/day, 49% carbohydrates) and an open control (OC) group without any supplement. The primary endpoint was tolerability. Patients were followed up over 4 weeks. Results: Gastrointestinal side effects were most frequent in the UHCFS group (75.0%), while loss of appetite was most frequent in the UHCCS group (35.3%). During intervention, patients gained +0.9 kg/month of body weight (IQR −0.9 to 1.5; p=0.03) in the HCFS group and +0.9 kg/month (IQR −0.8 to 2.0; p=0.05) in the UHCFS group. A non-significant trend for weight gain (+0.6 kg/month (IQR −0.3 to 1.9; p=0.08)) was observed in the UHCCS group. Patients in OC group continued to lose body weight (−0.5 kg/month, IQR −1.4 to 1.3; p=0.42). Interpretation: The findings suggest that HCSs frequently cause mild to moderate tolerability issues in patients with ALS, most notably gastrointestinal symptoms in high-fat supplements, and loss of appetite in high-carbohydrate supplements. All three HCSs tested are suited to increase body weight.